Rupa Gayah dalam Ritual Masyarakat Hindu di Desa Sembung, Mengwi, Badung - I Gde Suryawan; I Nyoman Duwika Adiana; I Kadek Jayanhti Riva Prathiwi (Sphatika: Jurnal Teologi, 2020)
Style is a collection of several satays and the bones of animals slaughtered (usually pigs) and then shaped so that they look attractive. In general the form of style can be divided into three namely the style of style, body style and peak style. Alas gayah consists of pig bones arranged like pigs while alive. On the body of the style is composed of several satay namely pengideran satay, satay that symbolizes the Gods Nawa Sanga (nine Gods who control the nine cardinal directions), pengurip-urip satay is satay which shows the amount of urip Dewata Nawa Sanga, and satay decoration is satay which symbolizes the contents of the nine directions of the compass; the world and functioning style decoration. The form of style in each region in Bali varies according to the taste of art and creativity of the maker, but has the same symbol and meaning, which is the symbol of the universe and is meaningful as a neutralizing the negative elements of the Great Bhuwana (nature) and Bhuwana Alit (humans).